Characterisation of Recycled Polyethylene Terephthalate as Partial Fine Aggregate Replacement Properties and Behaviour of Asphalt Mixtures for Road Pavements - Wan Mohd Nazmi, Wan Abdul Rahman; Mohammad Affendy, Omardin (Asian Research Publishing Network (ARPN), 2016)
The primany objective of this study is to evaluate optimum bitumen content and the characteristic of recycled polyethylene terephthalate (PET) as partial fine aggregate replacement in asphalt mixtures for road pavements by determining the rutting, fatigue and stiffness properties. The percentage of recycled PET replace fine aggregate in asphalt mixture start up 25% and bitumen content start from 4 to 6% of weight of asphalt mixture. The recycled plastic subsitute aggregate of sieve size aggregate between 3.36 and 1.18 mm content as follow with hot mix asphalt wearing course 14 (AC 14) in Standard Specification of Public Work Department (PWD) of Malaysia. The Indirect Tensile Stiffness Modulus Test (ITSM) was used to determine the optimum bitumen content of modified asphalt mixture and followed by the Repeated Load Axial Test (RLAT), and Indirect Tensile Fatigue Test (ITFT) both at 1800 cycles to investigate the rutting and fatigue properties of PET modified asphalt mixture consist of optimum bintumen content. The result shows the highest value stiffness modulus of 0% PET modified asphalt reach at 5.5% bitumen content. All the PET modified asphalt appears to be capable in resist rutting of road pavemet. Meanwhile 5% and 15% PET modified asphalt show more fatigue resistance than unmodified asphalt at 1800 cycles. In conclusion, the 5.5% bitumen content and additional 5% replacement aggregate of recycled PET plastic on asphalt mixture would enhance all engineering properties of asphalt mixture for road pavement